In command of history Churchill fighting and writing the Second World War - Reynolds, David 1952- (Basic Book, 2005)
As Britain's prime minister from 1940 to 1945, Churchill courageously led his nation and the world away from appeasement, into war, and on to triumph over the Axis dictators. His classic six-volume account of those years has shaped our perceptions of the conflict and secured Churchill's place as its most important chronicler. This book explains how Churchill wrote this masterwork, and in the process enhances and often revises our understanding of one of history's most complex, vivid, and eloquent leaders. It forces us to reconsider much received wisdom about World War II, and peels back the covers from an unjustly neglected period of Churchill's life, his "second wilderness" years, 1945-1951.--From publisher description.